Left orbital compartment syndrome and right anterior ischemic optic neuropathy in a patient with severe burns despite non-aggressive fluid resuscitation - Achmed Pircher; Sebastian Holm; Fredrik Huss (SAGE Publishing, 2021)
Introduction: Ophthalmological complications such as orbital compartment syndrome (OCS) and ischemic optic neuropathy are rare complications in patients with burns and have been described in patients where aggressive fluid resuscitation was performed. While OCS requires urgent surgical intervention, no current treatment is established to treat, or prevent, ischemic optic neuropathy in patients with burns. Methods: The authors report a case of a 38-year-old woman with flame burns including the periorbital regions who developed OCS on the left side and anterior ischemic optic neuropathy (AION) on the right side despite non-aggressive fluid resuscitation. Immediate lateral canthotomy combined with inferior cantholysis was performed on the left side. Discussion and Conclusion: OCS and AION need to be considered as potential complications even in critically ill patients with facial burns who do not receive aggressive fluid resuscitation. Whether an early surgical intervention will lower the risk of AION development is, however, speculative. Lay Summary Ophthalmological complications such as orbital compartment syndrome and ischemic optic neuropathy are rare complications in patients with burns and have been described in patients where aggressive fluid resuscitation was performed. We present a case of a critically ill patient with severe facial burns who developed orbital compartment syndrome on the left side and anterior ischemic optic neuropathy on the right side even though our patient did not receive aggressive fluid resuscitation. Our case is particular because both of these rare complications are seen in a single patient and neither received aggressive fluid resuscitation. The fact that the patient did not develop ischemic optic neuropathy on the side where the lateral canthotomy was performed (only on the side where the patient had orbital compartment syndrome), this case might raise the discussion of whether an early surgical intervention might lower the risk of ischemic optic neuropathy development in patients with facial burns.